2010
DOI: 10.1111/j.1467-9930.2010.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

A Refugee from Justice? Disparate Treatment in the Federal Court of Canada

Abstract: This article paints a troubling picture of disparate treatment in the Federal Court of Canada. Examining more than 600 immigration and refugee claims, the results link judicial action to litigants' representation, their demographics and national region, and the background and ideology of the judges involved. When compared with prior research in Canada and similar studies from the United States, the findings suggest that an applicant in search of a just result would do as well to hire an experienced lawyer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…By creating a measure that is specific to one area of law—here asylum decision making—we lessen the potential for multidimensionality in preferences to obscure our findings. Indeed, previous studies of asylum decision making in Canada have utilized both background characteristics and measures of ideology as determined by experts in asylum and immigration law in attempting to discern judges' policy predispositions (Gould, Sheppard, and Wheeldon ). Other early studies have also turned to the judges' background characteristics, arguing that they ‘reflect similar socialization processes and life experiences, which in turn produce similar attitudes and ultimately behavior (votes)’ (Gryski, Main, and Dixon , 528).…”
Section: Data Descriptionmentioning
confidence: 99%
“…By creating a measure that is specific to one area of law—here asylum decision making—we lessen the potential for multidimensionality in preferences to obscure our findings. Indeed, previous studies of asylum decision making in Canada have utilized both background characteristics and measures of ideology as determined by experts in asylum and immigration law in attempting to discern judges' policy predispositions (Gould, Sheppard, and Wheeldon ). Other early studies have also turned to the judges' background characteristics, arguing that they ‘reflect similar socialization processes and life experiences, which in turn produce similar attitudes and ultimately behavior (votes)’ (Gryski, Main, and Dixon , 528).…”
Section: Data Descriptionmentioning
confidence: 99%
“…Liberal critics are more likely to see the outcome as a function of inconsistent and idiosyncratic decision-making within the RDP. In their view, the outcome of someone's claim or appeal is far too dependent on the luck of the draw given considerable 'grant rate disparities' between adjudicators (Gould et al, 2010;Rehaag, 2007Rehaag, -8, 2012). 8 Ironically, the post-apartheid South African refugee determination system has precisely the opposite problem.…”
Section: Commonwealth and Comparative Politics 191mentioning
confidence: 95%
“…He will now appear before the RDP again where his lawyers will reportedly now argue that he will come to harm if returned to SA, 'because of fear of being attacked by black South Africans, and because he is now a well-known white South African' (Barbeau, 2012). Should his application be rejected, he will be able to institute a second round of appeals in the courts (Gould, Sheppard, & Wheeldon, 2010). Four years after first lodging what most legal commentators would see as a 'manifestly unfounded' claim and nine years after he first came to Canada on a temporary work permit, Huntley remains in the country.…”
Section: Commonwealth and Comparative Politics 191mentioning
confidence: 99%
“…This lack of transparency makes it impossible to assess whether applications are rejected because they are not seen as having merit, or whether, as the statistics would imply, the Federal Court has adopted an unofficial policy of only hearing a specific ratio of the cases available, which hovers steadily around 15 percent 47 . A recent study found that applicants who are represented by big law firms are more likely to be granted leave (Gould, Sheppard, and Wheeldon 2010), though these firms are also less likely to take on weak claims. The claimants who are granted leave go on to a full court hearing, but the prospect of reversal is extremely slim.…”
Section: The Canadian Rsd Regimementioning
confidence: 99%